La contaminación auditiva: Prácticas cotidianas que naturalizan el ruido como forma de comunicación en niños de básica primaria (2011)
This article aims to raise some questions that have naturalized noise as part of the communication in the classroom both between the dyad students and teachers. In order to do this, we analyze a a scheduled activity in the subject of Natural Sciences with fifth grade students of primary school, Roberto Garcia Peña, campus B, 2010 and 2011, afternoon shift, about the environmental pollution that can be identifed at the campus.  Some of the findings refer to the invisibility of noise as a potential contaminant inside and outside the classroom, as well as being seen as a normal feature in the performance of students by their very condition of  being children.